Perlindungan Hukum Terhadap Gelandangan dan Pengemis di Kota Batam sebagai Akibat Implementasi Peraturan Daerah Kota Batam Nomor 6 Tahun 2002 Tentang Ketertiban Sosial - Rufinus Hotmaulana Hutauruk; Dian Eka Putri (Journal of Law and Policy Transformation, 2021)
The presence of vagrants and beggars in Batam City is one of the problems of community welfare that is not easy to solve. Therefore, it is necessary to have a clear protection of the law against Vagrants and beggars in Batam City, not only to make efforts to combat vagrants and beggars but also to fulfill the rights of vagabonds and beggars that must be put forward by the Batam City Government. In this case, tackling the problems of vagabonds and beggars is the responsibility of the state. If you look at the contents of the 1945 Constitution of the Republic of Indonesia in Article 27 paragraph (2) which states that "Every citizen has the right to work and a decent living for humanity". In this case, the government is obliged to improve the condition of the community having problems with social welfare and ensure that every citizen has the right to a decent income. Whereas by providing legal protection, it is hoped that the squatters residing in Batam City can achieve a decent life and existence as citizens of the Republic of Indonesia. The research design that researchers used in this study was empirical legal research. The data analysis method used in this research is quantitative and qualitative research. Data were obtained by conducting interviews and observations with the Batam City Social and Community Empowerment Service Vagrants and Beggars in Batam City as a form of approach to vagabonds and beggars in their activities.From the results of research conducted by researchers, it shows that over the last four years (2016 - 2019) the number of vagrants and beggars in Batam City has tended to increase from year to year. Until 2019, the number of vagrants and beggars in Batam City has reached 588 people. The Batam City Social and Community Empowerment Service has carried out a non-physical prevention as a preventive legal protection, namely through print media, radio, videotron, provision of information through billboards in public places, which can be used to disseminate information and education to the public not to provide money to beggars on the streets, unless the money is given in its place, social counseling in places where vagrants and beggars are, so that vagrants and beggars do not wander and beg on the streets so that social order can be created. Furthermore, repressively carrying out control, outreach, data collection on vagrants and beggars to be followed up on the rehabilitation process. In this case, an analysis based on the Legal Protection Theory by Philipus M Hadjon, shows that the Batam City Social and Community Empowerment Service has not been effective in providing legal protection for vagrants and beggars in Batam City, because there are still many factors that become obstacles in providing legal protection. against vagrants and beggars in Batam City which is analyzed based on Soerjono Soekanto's Legal Theory of Legal Effectiveness